Effects of bodybuilding supplements on the kidney: A population-based incidence study of biopsy pathology and clinical characteristics among middle eastern men - Alaa Abbas Ali; Safaa E. Almukhtar; Dana A. Sharif; Zana Sidiq M. Saleem; Dana N. Muhealdeen; Michael D. Hughson (BMC Nephrology, 2020)
Abstract Background The incidence of kidney diseases among bodybuilders is unknown. Methods Between January 2011 and December 2019, the Iraqi Kurdistan 15 to 39 year old male population averaged 1,100,000 with approximately 56,000 total participants and 25,000 regular participants (those training more than 1 year). Annual age specific incidence rates (ASIR) with (95% confidence intervals) per 100,000 bodybuilders were compared with the general age-matched male population. Results Fifteen male participants had kidney biopsies. Among regular participants, diagnoses were: focal segmental glomerulosclerosis (FSGS), 2; membranous glomerulonephritis (MGN), 2; post-infectious glomeruonephritis (PIGN), 1; tubulointerstitial nephritis (TIN), 1; and nephrocalcinosis, 2. Acute tubular necrosis (ATN) was diagnosed in 5 regular participants and 2 participants training less than 1 year. Among regular participants, anabolic steroid use was self-reported in 26% and veterinary grade vitamin D injections in 2.6%. ASIR for FSGS, MGN, PIGN, and TIN among regular participants was not statistically different than the general population. ASIR of FSGS adjusted for anabolic steroid use was 3.4 (− 1.3 to 8.1), a rate overlapping with FSGS in the general population at 2.0 (1.2 to 2.8). ATN presented as exertional muscle injury with myoglobinuria among new participants. Nevertheless, ASIR for ATN among total participants at 1.4 (0.4 to 2.4) was not significantly different than for the general population at 0.3 (0.1 to 0.5). Nephrocalcinosis was only diagnosed among bodybuilders at a 9-year cumulative rate of one per 314 vitamin D injectors. Conclusions Kidney disease rates among bodybuilders were not significantly different than for the general population, except for nephrocalcinosis that was caused by injections of veterinary grade vitamin D compounds.